Knee flexion not hip extension strength is persistently reduced following hamstring strain injury in Australian football athletes: Implications for periodic health examinations - Charlton, P. C.; Raysmith, B.; Wollin, M.; Rice, S.; Purdam, C.; Clark, R. A.; Drew, M. K. (Journal of Science and Medicine in Sport, 2018)
Objectives: Determine whether clinically feasible tests of isometric lower limb strength and range of motion (ROM) in Australian Football (AF) athletes are useful in Periodic Health Examinations to identify persistent deficits following hamstring strain injury (HSI). Design: Case-control. Methods: Thirty-seven male, semi-professional AF athletes (mean±SD; age, 20.2±2.9years; height, 1.7±0.5m; mass, 81±9.2kg) participated, ten athletes (37%) reported HSI within the previous three seasons of competition. Comparisons of pre-season isometric knee flexion and hip extension strength variables (peak force, torque and torque normalised to body mass) and hip, knee and ankle ROM measures were made between athletes with and without past-history of HSI using linear mixed-effect models. A logistic regression evaluated whether any of the outcome measures could differentiate athletes with a past-history of HSI. Results: Knee flexion peak force, torque and torque normalised to body mass were significantly reduced in athletes with a past-history of HSI (coefficient, 95% CI) (-44.8N, -86.3 to -3.3), (-22.2Nm, -40.5 to -3.7) and (-0.2Nmkg-1, -0.4 to 0.0) respectively. Knee flexion peak torque normalised to body mass (Nmkg-1) approached significance as a test was able to differentiate athletes with history of HSI (p=0.068). There were no differences between groups for any hip extension strength or lower limb ROM outcome measures. Conclusions: Deficits in isometric peak knee flexion strength persist for up to three seasons following HSI in AF athletes. Isometric knee flexion strength testing may be a clinically feasible option for Periodic Health Examinations and inform tertiary injury prevention strategies. ABSTRACT FROM AUTHOR